2014
DOI: 10.1128/aac.02636-14
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Carbapenem-Resistant Klebsiella pneumoniae: Tracking Molecular Epidemiology and Outcomes through a Regional Network

Abstract: m Carbapenem resistance in Gram-negative bacteria is on the rise in the United States. A regional network was established to study microbiological and genetic determinants of clinical outcomes in hospitalized patients with carbapenem-resistant (CR) Klebsiella pneumoniae in a prospective, multicenter, observational study. To this end, predefined clinical characteristics and outcomes were recorded and K. pneumoniae isolates were analyzed for strain typing and resistance mechanism determination. In a 14-month per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
148
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(158 citation statements)
references
References 23 publications
10
148
0
Order By: Relevance
“…For example, our findings are consistent with the observations in previous studies that described most patients to be elderly, with multiple comorbidities (2,57,61) and with UTI and bloodstream infections the most frequently reported (42,57,(61)(62)(63). Several studies evaluating risk factors for CR-Kp acquisition found exposure to health care and previous antimicrobial use as the most significant risks (3,9,(61)(62)(63)(64)(65)(66)(67)(68)(69).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…For example, our findings are consistent with the observations in previous studies that described most patients to be elderly, with multiple comorbidities (2,57,61) and with UTI and bloodstream infections the most frequently reported (42,57,(61)(62)(63). Several studies evaluating risk factors for CR-Kp acquisition found exposure to health care and previous antimicrobial use as the most significant risks (3,9,(61)(62)(63)(64)(65)(66)(67)(68)(69).…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with our findings that medical history showing surgery, hospitalization, antibiotic use prior to infection, and the presence of invasive medical devices at the moment of infection were associated with CR-Kp acquisition (Table 1). Meanwhile, we found an overall 34% mortality rate, in accordance with previous reports of rates that varied from 6% to 60% depending on the severity of infection (9,42,(68)(69)(70). Interestingly, our study revealed a highly heterogeneous genetic background of CR-Kp strains, and CR-Kp from different clones displayed distinct clinical characteristics in our local epidemiology.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These patients also frequently have multiple comorbidities, poor functional status, recent intravenous antibiotic exposure (within 90 days), and indwelling devices (urinary catheter, mechanical ventilation, indwelling lines). Patients that recover from their acute hospitalization are frequently discharged to LTCFs or LTACHs, thus contributing to a viscous cycle [10,12]. LTACHs play an important role in the regional epidemiology of CRE.…”
Section: Introductionmentioning
confidence: 99%
“…coli expressing CTX-M-type enzymes containing ESBLs have been increasingly seen in the community [12,[22][23][24][25][26]. Residency of a long-term care facility has been recognized as a prominent risk factor for acquisition of ESBL infections in the community.…”
Section: Introductionmentioning
confidence: 99%